Gallbladder squamous cell carcinoma: An analysis of 1084 cases from the National Cancer Database. Issue 4 (8th June 2020) - Ayabe, Reed I.; Wach, Michael M.; Ruff, Samantha M.; Diggs, Laurence P.; Martin, Sean P.; Wiemken, Timothy; Hinyard, Leslie; Davis, Jeremy L.; Luu, Carrie; Hernandez, Jonathan M.
Abstract: Background/Objectives: Gallbladder squamous cell carcinoma (SCC) is an uncommon malignancy whose rarity has made it particularly challenging to study. We utilized a national database to shed light on the clinicopathologic characteristics, management patterns, and survival associated with these tumors. Methods: Patients with gallbladder SCC were identified in the National Cancer Database. Clinicopathologic and treatment characteristics were recorded and compared with adenocarcinoma for context. Univariate and multivariable survival analyses were completed for patients who underwent resection. Results: Overall, 1084 patients with SCC and 23 958 patients with adenocarcinoma were identified. Compared with those with adenocarcinoma, patients with SCC had higher grade tumors ( P  < .001) and were diagnosed at a later stage ( P  < .001). Patients with SCC were more likely to undergo radical cholecystectomy (17% vs 9%;  P  < .001), but had a higher rate of margin positivity (36% vs 29%;  P  < .001). SCC histology was associated with worse survival compared with adenocarcinoma, even after adjusting for R0 resections (13 vs 29 months;  P  < .001). On multivariable analysis, SCC histology was independently associated with abbreviated survival ( P  = .003). Conclusions: Gallbladder SCCs are aggressive cancers that often present at an advanced stage. Complete surgical extirpation should be pursued when feasible. However, prognosis is worse than that of adenocarcinoma, even after R0 resection.